Features and Possible Applications of Plant Lipid-Binding and Transfer Proteins - Daria N. Melnikova; Ekaterina I. Finkina; Ivan V. Bogdanov; Andrey A. Tagaev; Tatiana V. Ovchinnikova (Membranes, 2022)
In plants, lipid trafficking within and inside the cell is carried out by lipid-binding and transfer proteins. Ligands for these proteins are building and signaling lipid molecules, secondary metabolites with different biological activities due to which they perform diverse functions in plants. Many different classes of such lipid-binding and transfer proteins have been found, but the most common and represented in plants are lipid transfer proteins (LTPs), pathogenesis-related class 10 (PR-10) proteins, acyl-CoA-binding proteins (ACBPs), and puroindolines (PINs). A low degree of amino acid sequence homology but similar spatial structures containing an internal hydrophobic cavity are common features of these classes of proteins. In this review, we summarize the latest known data on the features of these protein classes with particular focus on their ability to bind and transfer lipid ligands. We analyzed the structural features of these proteins, the diversity of their possible ligands, the key amino acids participating in ligand binding, the currently known mechanisms of ligand binding and transferring, as well as prospects for possible application.